Low carbohydrate ketogenic diets reduce cardiovascular risk factor levels in obese or overweight patients with T2DM: A meta-analysis of randomized controlled trials - Luo, Wei; Zhang, Jin; Xu, Dan; Zhou, Yao; Qu, Zhen; Yang, Qin; Lv, Qiujv (Frontiers in Nutrition, 2022)
Abstract Background: The purpose of this meta-analysis was to explore the effects of low-carbohydrate ketogenic diets on cardiovascular risk factors in overweight or obese patients. However, systematic studies on how low-carbohydrate ketogenic diets improve cardiovascular risk factors in obese or overweight patients are rare. Methods: We systematically searched PubMed, EMBASE, Web of Science, OVID, and Cochrane Library databases (last updated in September 2022) for randomized controlled trials (RCTs) which recruited overweight or obesity patients on ketogenic diets in order to control cardiovascular risk factors (blood glucose, weight, and lipids). The overall effect size for continuous variables was expressed as a weighted standardized mean difference (SMD) with a confidence interval of 95%. Considering type 2 diabetes mellitus (T2DM) status at baseline, subgroup analyses were performed when appropriate, based on T2DM comorbidity among patients. The effect model was selected according to heterogeneity. Results: We finally selected 21 studies. Low carbohydrate ketogenic diets exerted a greater impact on cardiovascular risk factors in overweight/obese patients with T2DM when compared with those on non-ketogenic diets, with lower fasting plasma glucose(FPG) (SMD, −0.75; P＜0.001)and hemoglobin A1c (HbA1c) (SMD, −0.53; P＜0.001) levels identified. Low-carbohydrate ketogenic diets significantly reduced body mass index (BMI) (SMD, −2.27; P = 0.032), weight (SMD, −6.72; P＜0.001), and waist circumference (SMD, −4.45; P = 0.003) in overweight/obese patients with T2DM. Also, ketogenic diets improved lipid profiles in these patients; triglyceride (TG) (SMD, −0.32; P = 0.013) levels were lowered and high density lipoprotein (HDL) showed an upward trend with the P value close to critical (SMD, −0.32; P = 0.052). In general, irrespective of diabetic status at baseline, ketogenic diets were more effective in reducing TG (SMD, -0.2; P = 0.02) and increasing HDL (SMD, 0.11; P = 0.03) levels when compared with non-ketogenic diets. Conclusions: Low-carbohydrate ketogenic diets effectively improved cardiovascular risk factors (blood glucose, weight, and lipids) in overweight or obese patients, especially those with T2DM when compared with non-ketogenic diets.